2019
DOI: 10.1177/2329496519875484
|View full text |Cite
|
Sign up to set email alerts
|

Refugees’ Transnational Practices: Gay Iranian Men Navigating Refugee Status and Cross-border Ties in Canada

Abstract: Despite the rise in displaced population numbers, refugees’ transnational lives, and those of sexual-racial minority refugees in particular, have remained at the margins of transnational migration studies. In this article, I focus on the case of gay Iranian refugees in Canada and analyze their pre-migration transnational lives and understandings of the asylum process, their post-migration transnational ties, and their activism practices. I underline refugees’ transnational agencies and argue against the rhetor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 86 publications
0
17
0
6
Order By: Relevance
“…Such workshops provided in the native language of LGBTQ+ refugees by facilitators who also have the knowledge and familiarity with their intersectional background can largely improve the integration of LGBTQ+ refugees. While Karimi's (2018Karimi's ( , 2019aKarimi's ( , 2019bKarimi's ( , 2020 work mainly focused on gay Iranian refugees, which does not constitute for the larger group of ME-LGBTQ+ refugees, his findings can largely apply in their context and reveal similar implications and impacts of their intersectional identities on their integration experiences.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Such workshops provided in the native language of LGBTQ+ refugees by facilitators who also have the knowledge and familiarity with their intersectional background can largely improve the integration of LGBTQ+ refugees. While Karimi's (2018Karimi's ( , 2019aKarimi's ( , 2019bKarimi's ( , 2020 work mainly focused on gay Iranian refugees, which does not constitute for the larger group of ME-LGBTQ+ refugees, his findings can largely apply in their context and reveal similar implications and impacts of their intersectional identities on their integration experiences.…”
Section: Literature Reviewmentioning
confidence: 95%
“…For example, the author found that participants continued to keep strong ties with their families and social networks at home by adapting to hiding their sexual identities and keep a distance between their ties to home and their lives in Canada. Karimi (2019bKarimi ( , 2020 argues against the assumed homogeneity of the group of ME-LGBTQ+ refugees and recommended, as a response to their intersectional experiences, "the immediate creation of safe spaces in refugee welcome centers. I also recommend developing pre-arrival workshops about life in Canada for racialized LGBT refugees" (Karimi, 2020, p146).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As globalization of LGBT rights increases, so too does the transnational flow of information, cultural content, and overall visibility (Ayoub, 2016;Ayoub & Garretson, 2017). For example, access to gay characters in film and gay content on the Internet contributed toward Iranian refugees to seek sexual freedom and affirming political environments in the West (Karimi, 2020). Altogether, these developments in the global environment help shift sexuality, which has always been in the background of migratory decisions, to the foreground.…”
Section: Our Interventionmentioning
confidence: 99%
“…Digital media technologies can assist during the move from one country to another, such as in the case of queer refugees temporarily living in Turkey while in transit from the Arab Middle East to the European Union (Bayramoğlu & Lünenborg, 2018) or while in transit from Iran to Canada (Karimi, 2020). The information gathered in transit might affect the final destination of the migrant (Lennes, 2020).…”
Section: During the Movementioning
confidence: 99%
“…The information gathered in transit might affect the final destination of the migrant (Lennes, 2020). Practical information can be sent back to queer contacts in one's country of origin, thus sparking new migrations along the same (or a different) trajectory (Karimi, 2020). In sum, digital media facilitate interpersonal networks that assist with information-gathering and other practical logistics of migration while simultaneously fostering a sense of belonging to a larger LGBTQ community.…”
Section: During the Movementioning
confidence: 99%